Penetapan Harga Karet dalam Perspektif Ekonomi Islam dan Dampaknya terhadap Pendapatan Petani (Studi pada Masyarakat Desa Gajah Mati Kabupaten Bengkulu Tengah) - Tari Diana Putri; Nurul Hak; Romi Adetio Setiawan (Ekonomis: Journal of Economics and Business, 2023)
Price is a determination of the value of goods or services in the form of money and must reflect the profits between the buyer and seller. Islamic economics teaches that market prices are in accordance with the sunnatullah will of Allah, namely determined by the law of supply and demand which cannot be intervened by any party. Then the influence on price setting on income becomes one of the benchmarks for improving people's welfare. The aim of setting prices is to balance prices in the market in order to maintain benefits so that no one feels wronged. This research uses a qualitative research approach using field research or Field Research. The results of this research indicate that rubber price determination in Gajah Mati Village is viewed in Islamic economics based on the theory put forward by Ibnu Taimiyah as a Muslim scientist figure which is not in accordance with the concept of Islamic economics, because there is intervention from various other parties besides that there are still acts of fraud being committed. . So there are parties who feel oppressed, namely farmers and middlemen who feel disadvantaged. The impact on farmers' income in the community in Gajah Mati Village is very influential. Where people's income is used to meet daily needs including primary, secondary and tertiary needs which are still inadequate. This is caused by farmers' income decreasing due to rubber prices which often experience price changes.